Limas Home Interior Design Conservation Served as A Cultural Heritage In The Balaputra Dewa Museum Hall Palembang - Margareth Trevina Nugrahani; Rahmanu Widayat (Faculty Of Arts and Design Sebelas Maret University, 2025)
With the advancement of time and rapid urbanization, many traditional houses have suffered damage or been abandoned. One region in Indonesia renowned for its history and heritage is the city of Palembang, the oldest city in Indonesia. As the oldest city, Palembang holds a wealth of historical sites and artifacts, including traditional Palembang houses known as limas house. According to historical records, there are approximately 200–300 limas house in Indonesia. Preserving these houses is essential as they strengthen the regional identity of Palembang and contribute to its uniqueness. This study aims to assess the interior design compatibility of limas house at the Balaputra Dewa Museum with the criteria of heritage buildings and to evaluate the conservation efforts applied to the interior design of limas house as a cultural heritage object in the Balaputra Dewa Museum area. The research employs a descriptive qualitative method with a case study approach. The results indicate that the limas house employs five out of six types of building conservation. However, there have been errors in installing some structural components of the limas house, and several parts remain damaged. Despite this, the values and functions of the limas house interior design as a cultural heritage remain intact. The interior design of the limas house at the Balaputra Dewa Museum aligns with cultural heritage building criteria based on cultural heritage parameters. Nevertheless, the conservation efforts for the limas house in the Balaputra Dewa Museum area are considered suboptimal in implementation. Keywords : Balaputra Dewa, Conservations, Interior Design, Limas House.